Strategi Komunikasi Pemasaran Marvel Studios,LLC: Deadpool and Wolverine 2024 - Qomariyah, Annisa Lailatul; Purbantina, Adiasri Putri (P3M Politeknik Negeri Media Kreatif, 2025)
Movies have become a dominant medium in the entertainment industry, serving as entertainment and a vehicle for information dissemination. Effective marketing strategies are crucial for promoting films and driving economic growth within this sector. Marvel Studios, LLC has employed a successful Integrated Marketing Communication (IMC) approach, as outlined by Kotler and Armstrong, to promote their Deadpool and Wolverine films. Using a qualitative research methodology, this study descriptively analyzes the implementation of IMC dimensions within Marvel Studios' marketing strategies. The results demonstrate that the company has effectively applied all five IMC dimensions to enhance its reputation, promote films, and foster consumer loyalty. Marvel Studios' strategic use of social media platforms has been particularly impactful, maximizing the reach and effectiveness of their promotional efforts.